Municipal solid waste landfill site selection using Multi-Criteria Decision Making and GIS: case study of Bursa province - Yildirim, Volkan; Memisoglu, Tugba; Bediroglu, Sevket; Colak, H. Ebru (Journal of Environmental Engineering and Landscape Management, 2018)
Rapid population growth, economic development and industrialization have created many problems related to municipal solid waste management (MSWM) in developing countries like Turkey. Solid waste disposal has become mandatory because of increasingly common factors such as global warming and contamination of water resources. In recent years, this situation has revealed the need for effective management of solid waste. Suitable site selection requires evaluation and analysis of multiplefactor. Therefore, it is very important that the design of landfill site selection take into account environmental, economical and sociologicalfactors. In order to do this, the Geographical Information System (GIS) used with Multi Criteria Decision Making (MCDM) techniques is a useful tool for creating a model. One such MCDM is the Spatial-integrated Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). In this study, TOPSIS was applied to integrate environmental, economical and sociological sensitivity into determine alternative solid waste landfill sites for Bursa Province, Turkey. Using the data obtained by comparing the geo-statistics, six of the most suitable landfill areas were determined. In the final stage, as a result of this study, the Kayapa district was identified as the most suitable landfill area.